DRUGS AND SUBSTANCE ABUSE IN KENYAN SECONDARY SCHOOLS: IS IT A REALITY?. - Ngesu, Lewis M. (IJRDO- Journal of Educational Research, 2017)
Drug abuse has become a global phenomenon affecting almost all countries though the degree and individuality effects and impacts show a discrepancy depending on the country in question. Kenya has not escaped the phenomena, drug abuse has permeated all stratums of Kenyan people; many of the Kenyan youths, especially those in secondary schools, are falling prey to drug and substance abuse. This has ruined their life as a result of addiction. Today it has become an African problem to the extent that a monthly hardly passes without media reports on large quantities of drugs having been intercepted in a number of African cities and towns. The results of the study indicated that students abused drugs for varied reasons and the commonly abused drugs were alcohol, bhang, miraa, tobacco and kuber. The study recommended that guidance and counseling in schools be enforced and that strict disciplinary measures be enforced by teachers to curb the vice. Policy makers should also focus their efforts on addressing administrative disparities of principals’ leadership capacities across urban, suburban and rural setting